2023
DOI: 10.3389/fmicb.2022.1091288
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution, traditional and modern detection, diagnostic, and management approaches of Rhizoctonia solani associated with legume crops

Abstract: Sustainable development relies heavily on a food system that is both safe and secure. Several approaches may lead to sustainability and food safety. An increase in the cultivation of legume crops is one of the approaches for enhancing agricultural viability and ensuring adequate food supply. Legumes may increase daily intake of fiber, folate, and protein as substitutes for meat and dairy. They are also crucial in various intercropping systems worldwide. However, legume production has been hampered by Rhizocton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 154 publications
0
10
0
Order By: Relevance
“…The symptoms associated with R. solani ( Table 1 ) infection are various and change based on the host: they include hypocotyl, crown, stem and root rot, blights, wire stem, and damping off [ 72 ]. Being a seedborne pathogen, it can lead to seed rot and decay, pre-emergence damping off, and germination failure [ 73 , 74 ]. Moreover, it has been demonstrated that R. solani can be preserved in different parts of the seeds, including the seed coat, endosperm, and embryos [ 75 ].…”
Section: Seedborne Fungi and Oomycetes Of Principal Leguminous Cropsmentioning
confidence: 99%
See 2 more Smart Citations
“…The symptoms associated with R. solani ( Table 1 ) infection are various and change based on the host: they include hypocotyl, crown, stem and root rot, blights, wire stem, and damping off [ 72 ]. Being a seedborne pathogen, it can lead to seed rot and decay, pre-emergence damping off, and germination failure [ 73 , 74 ]. Moreover, it has been demonstrated that R. solani can be preserved in different parts of the seeds, including the seed coat, endosperm, and embryos [ 75 ].…”
Section: Seedborne Fungi and Oomycetes Of Principal Leguminous Cropsmentioning
confidence: 99%
“…R. solani is usually preserved in the soil or plant debris as sclerotia or, in seeds, in the form of mycelium. Otherwise, the teleomorph form permits the propagation of basidiospores that are carried by the wind and rain, but this form is rarely encountered in fields [ 74 ]. R. solani overwinters in the soil, and the infection starts with mycelium germination through the plant epidermis.…”
Section: Seedborne Fungi and Oomycetes Of Principal Leguminous Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…This inoculum is difficult to be controlled using chemicals. Rhizoctonia solani Kuhn infects several crops including soybean, alfalfa, peanut, and mung bean [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…R. solani may limit legume production because this pathogen causes blight, damping off and rotting disease [1,3]. Infection on soybean may occur at any growth stage and severe damage can be found at seedling growth.…”
Section: Introductionmentioning
confidence: 99%